Monetary policy rules and wage bargaining structure in a New-Keynesian general equilibrium model with strategic interaction between unions and monetary authority - Oreiro, José Luis da Costa; Basílio, Flávio Augusto Corrêa (Práticas de Administração Pública, 2023)
The objective of this article is to present a New Keynesian general equilibrium model in which the multiplicity of wage and price setters in a framework of strategic interaction between the private sector and monetary authority is a sufficient condition for non-neutrality of the monetary policy rule. In this theoretical framework we can show that (i) strategic interaction between monetary authority and labor unions produce the so-called “Calmfors-Driffil effect” in which different levels of centralization in wage bargains allowed to reach different results in terms of equilibrium unemployment rate; (ii) a higher level of conservatism in the conduction of monetary policy; i.e. higher weight for deviations of price inflation from the target in the monetary policy rule, for a given level of centralization of wage bargaining, produce better outcomes in terms of inflation and unemployment. These results shows that there is a trade-off between centralization of wage bargaining and a tighter monetary policy rule: the more centralized is the wage bargaining structure lower can be the weight of inflation in the monetary policy rule that allowed Central Bank could be to achieve some target level of inflation and unemployment. So, the model proposed here shows that income policies can be, in principle, such effective as monetary policy as a device for improve macroeconomic performance of capitalist economies.